Mining Sequence Compliance and Production Performance in an Open-Pit Coal Mine: A Case Study of Pit Rista, South Sumatra - Ambun Qodri; Fariz Aditya; Fadhilah Fadhilah; Tri Gamela Saldy (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2026)
This study assesses coal and overburden production efficacy for the mining sequence at Pit Rista, PT Dewa Sukses Mandiri, South Sumatra, during July and August 2025, and recommends operational enhancements to facilitate production objectives in the following months. The investigation was prompted by the inability to meet monthly production targets, as evidenced by insufficient effective working hours, excessive downtime, low equipment availability, and discrepancies between planned and actual mining progress. A quantitative evaluative method was employed utilizing primary data consisting of loading and hauling cycle durations, alongside secondary data such as production reports, working hours, downtime records, mine design, and mining sequence plans. The examination encompassed equipment productivity, job efficiency, match factor, physical availability (PA), use of availability (UA), Pareto analysis of downtime, and a comparison between planned and actual implementation of the mining sequence. The findings indicate that production deficits in July and August 2025 were mostly attributable to diminished effective working hours resulting from operational and mechanical delays, low PA and UA values, and discrepancies between the planned mining sequence and actual field execution. In July, the primary cause of lost time was the lack of hauling help, however in August, weather-related delays emerged as the principal limitation. These conditions impeded mining advancement and diminished overall output efficacy. In light of these findings, production optimization should prioritize enhancing mining sequence execution, reinforcing equipment maintenance and oversight, reconfiguring pit front and haul road geometry, and regulating haul road gradients to minimize downtime and enhance operational efficiency.